MORPHOLOGICAL, CONTROVERSIAL AND LITERARY REVIEW OF SHANKHPUSHPI - Naveen, *Kumar; Suresh, Chaubey; Sanjay Kumar, Singh; Ramesh Chandra, Tewari (International Journal of Ayurveda and Pharma Research, 2016)
India is enriched in diversity of flora since ages. The ancient professionals have kept records of their work related to the plants and their works are a source of research today. Shankhpushpi is a well known herb since the most primitive works on Ayurveda have its therapeutic uses well elaborated and its morphological features well described. Later on, controversies erupt as locals in different parts of India used different plant species in the name of Shankhpushpi. Mainly four different plant species are considered in the name Shankhpushpi across India. These are Convolvulus pluricaulis, Clitorea ternatea, Evolvulus alsenoides and Canscora decussata. Shankhpushpi is a widely used herbal drug in the management of cognitive disorders from the times of Acharya Charak (200 BC) till today. Shankhpushpi has been categorized as a Medhya drug i.e. an efficient brain tonic by all ancient texts with no exceptions. Modern researches have established Shankhpushpi as an effective drug to be used either single or in combination, in the treatment of central nervous system disorders and boosting intellect. This article is an attempt to review the morphological features of the plant taken as Shankhpushpi along with the review of literature regarding the therapeutic values described from 200 BC to 20th century.